The validity of the heat tolerance test in prediction of recurrent exertional heat illness events. Issue 6 (June 2018) - Schermann, Haggai; Heled, Yuval; Fleischmann, Chen; Ketko, Itay; Schiffmann, Nathan; Epstein, Yoram; Yanovich, Ran
Abstract: Objectives: Heat-tolerance-testing (HTT) protocol is used as a screening test for secondary prevention of exertional heat illness (EHI) in the military. Subjects whose test results are positive (heat-intolerant, HI) are presumed to be at higher risk of repeated EHI events than heat-tolerant subjects (HT) and are therefore prevented from return to combat duty, but may return to unsupervised recreational activity. Our aim was to determine, whether HTT results predict the risk of repeated episodes of exertional heat illness (EHI). Design: Retrospective cohort. Methods: One-hundred-forty-five subjects (110 HT, 35 HI) who were diagnosed with an EHI event by a physician and underwent HTT during 2008–2015 were contacted and asked about recurrence of EHI. Incidence of recurrent events was reported as number of cases per 1000 person-years. Ratio of events among HI and HT individuals was presented as rate ratio (RR) and its 95% confidence interval. Results: Of the 145 patients, six (4.1%) had experienced recurrent EHI events (10.63 per 1000 PY): four HI subjects (11.4%, 26.6 per 1000 PY) and two HT (1.8%, 4.8 per 1000 PY) (RR = 5.504, CI 95% = 1.01–30, p = 0.027). Only one of the six recurrent events was a heat stroke (HT individual), other five were heat exhaustions. Sensitivity, specificity and diagnostic accuracy of HTT were 66.7%, 77.7% and 77.2%, respectively. Conclusions: The risk of EHI recurrence is measurable and can be discussed with patients before they return to sports. A referral to HTT can be considered, as negative HTT result is associated with substantial and significant EHI risk reduction.